Assessment of a novel solid oxide fuel cell tri-generation system for building applications - Elmer, Theo; Worall, Mark; Wu, Shenyi; Riffat, Saffa (Elsevier, 2016)
The paper provides a performance analysis assessment of a novel solid oxide fuel cell (SOFC) liquid desiccant tri-generation system for building applications. The work presented serves to build upon the current literature related to experimental evaluations of SOFC tri-generation systems, particularly in domestic built environment applications. The proposed SOFC liquid desiccant tri-generation system will be the first-of-its-kind. No research activity is reported on the integration of SOFC, or any fuel cell, with liquid desiccant air conditioning in a tri-generation system configuration. The novel tri-generation system is suited to applications that require simultaneous electrical power, heating and dehumidification/cooling. There are several specific benefits to the integration of SOFC and liquid desiccant air conditioning technology, including; very high operational electrical efficiencies even at low system capacities and the ability to utilise low-grade thermal energy in a (useful) cooling process. Furthermore, the novel tri-generation system has the potential to increase thermal energy utilisation and thus the access to the benefits achievable from on-site electrical generation, primarily; reduced emissions and operating costs.